The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1741-5705.2010.03783.x
|View full text |Cite
|
Sign up to set email alerts
|

Hope, Tropes, and Dopes: Hispanic and White Racial Animus in the 2008 Election

Abstract: One of the central questions surrounding the 2008 presidential election is the role of race in shaping electoral choice among non‐Hispanic whites, and whether race played an equivalent role among Hispanics, whose willingness to vote for an African American candidate was raised as an uncertainty during the primary campaign. The authors argue that, beyond the usual association of racial sentiment with party preference, the effect of Obama's race on the 2008 election is significant, but substantially smaller amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…See Ditonto, Lau, and Sears (2013) for results similar to ours. Segura and Valenzuela's (2010) analysis of vote choice in 2008 yields results that differ somewhat from ours, as they do not use a measure of indifference to black suffering-this measure, as we show, has comparable associations with vote choice across Latinos and non-Hispanic whites. 9.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…See Ditonto, Lau, and Sears (2013) for results similar to ours. Segura and Valenzuela's (2010) analysis of vote choice in 2008 yields results that differ somewhat from ours, as they do not use a measure of indifference to black suffering-this measure, as we show, has comparable associations with vote choice across Latinos and non-Hispanic whites. 9.…”
mentioning
confidence: 66%
“…While these studies have made valuable contributions, in some cases the primary goal of these studies is to consider white prejudice against blacks; accordingly, Latino attitudes toward blacks are reported as a secondary result and are not investigated as thoroughly as white attitudes. Among the studies that are more centered on the impact of prejudice among Latinos, the scope is mostly limited to the analysis of a single election (Segura and Valenzuela 2010;Tesler and Sears 2010).…”
Section: Latino Attitudes Toward Blacks: Current Literature and Our Amentioning
confidence: 99%
See 1 more Smart Citation
“…Others have found significant evidence of hostile attitudes toward Blacks and policies targeting Blacks among Latinos (e.g., Gay, ; Kaufmann, ; Lopez & Pantoja, ; McClain, ) and that Latinos see themselves as having more in common with Whites than Blacks (McClain et al., ). On the other hand, Latinos and African Americans have been shown to have similar policy beliefs and ideological positions (Hero & Preuhs, ; Kaufmann, ), and work by both Barreto, Segura, and Valenzuela () and Segura and Valenzuela () find that racial sentiments played little role in determining Latinos' attitudes toward Obama and vote choice in 2008.…”
Section: Methods and Hypothesesmentioning
confidence: 99%
“…Segura and Valenzuela (2010) showed that Racial Resentment had a significant, negative effect on Obama's candidacy. Similarly, Pasek et al (2009) concluded that anti-African American racism reduced Obama's vote share (see also Redlawsk et al 2010).…”
Section: Introductionmentioning
confidence: 97%